Pengembangan Game Edukasi Labelled Diagram Untuk Pengenalan Bahasa Asing Pada Anak Kelompok B Di TK Negeri Pembina Mataram - Indri Iinpalina; Gunawan Gunawan; Baik Nilawati Astini; Fahruddin Fahruddin (Indonesian Publication Center, 2024)
This research aims to develop an educational labelled diagram game to assist group B children at TK Negeri Pembina Mataram in learning a foreign language (English) that is feasible, practical, and effective. This game is expected to increase children's interest and ability in learning a foreign language in a fun and effective way. The research method used is R&D (Research and Development) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The labelled diagram educational game is developed through 5 stages: Analysis, Design, Development, Implementation, Evaluation. The subjects in this study were group B children totaling 14 children. Data collection techniques used observation, documentation, and questionnaires. Data analysis was carried out descriptively qualitatively. The results showed that the labelled diagram educational game succeeded in improving early childhood foreign language recognition skills. This is evidenced by an increase in the percentage of children's foreign language recognition skills from 71% with the Developing as Expected (DAE) criteria in trial I to 93% with the Developing Very Well (DVW) criteria in trial II marked by indicators 2 and 5 which previously had the lowest percentage, now have the most significant increase compared to trial I. Validation from media experts and material experts obtained a percentage of 95% with the